EFFECT OF AVOCADES TO LDL CHOLESTEROL AS A PREVENTIVE RISK ATHEROSCLEROSIS (Peer Reviewer) - Shahrul Rahman (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Cardiovascular disease is the highest cause of death in most developing countries. Hypercholesterolemia, especially high LDL is a risk factor for cardiovascular disease can be overcome through a good diet. Avocados are rich in fat.